INFLUENCING FACTORS ON FINANCIAL PERFORMANCE OF BASIC MATERIALS SECTOR COMPANIES LISTED IN IDX - Trivena, Christy; Nariman, Augustpaosa (International Journal of Application on Economics and Business, 2025)
In the financial realm, financial performance plays a key role in describing compaies’s finanncial condition. The capacity to generate profits provides insight into the company'sperformance, which serves as a key element in evaluating itsfinancial performance. This study’s purpose is to understand how the influence of independent variables consisting of sales growth, firm size, liquidity, and leverage on dependent variable, namely financial.performance in basic materials sector.companies officially listed on the IDX /Indonesia Stock Exchange in 2021-2023. This study uses 129 observational data taken using purposive sampling mothod, and the obtained samples that meet the predetermined requirements/criteria are 43 companies, also will be studied further. Secondary type data was used in this study data acquisition comes from the official IDX website and other companies’s websites. Multiple linear regression method was the analysist in this study based on the Econometric-Views (E-views) version 12 program. According to the results of the data processing that has been carried out, the results indicate that the sales growth and firmsize variables have a significant positive impact on financialperformance, meanwhile the liquidity and leverage variables have a significant negative impact on financialperformance. It is expected that the findings of this study will serve as a reference for practitioners in their decision-making.